Parental Accompaniment and Its Role in Promoting Children’s Public Health - Boudour, Abd el Malek (Journal of Ecohumanism, 2026)
The primary aim of this paper is to become thoroughly acquainted with the facts related to parental accompaniment, and as a research priority in this paper is to determine its role in promoting children’s public health within the family environment. Various studies confirm that a harmonious and healthy development of the child can only be achieved through the family environment, where particular attention is paid to the child’s personality, including its weaknesses and strengths, and where both apparent and latent abilities are invested to assist the child throughout their developmental stages, without neglecting the basic health, psychological, and social difficulties and problems that may emerge later.